THE INFLUENCE OF INTEREST PAYMENT ABILITY TO RELATION BETWEEN COMPANY RISK AND DEBT LEVEL - Octavia, Angelica; Dananjaya, Yanuar (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
Trade off theory suggests that as business risk increases (decreases), company debt level will decrease (increase). This is because companies compensate for higher business risk with lower debt level as debt is riskier than equity. Companies also avoid higher interest rate charged for debt to companies with higher business risk. We found that company’s ability to pay for interest expense mitigate the negative relation between business risk and debt level among manufacture companies in Indonesia. As the ability to pay interest expenses increases, bankruptcy risk decreases. Lenders will perceive the company as a low-risk company, even though business risk is high. Another mechanism is that the ability to pay interest acts as a signal that the company has lower risk than what business risk suggests. The result is lower interest rate that leads to higher debt level.